2015
DOI: 10.4236/psych.2015.61004
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Homicidal Fantasies among Finnish University Students

Abstract: Homicidal behavior is sex-linked. But research comparing male and female homicidal fantasies is sparse even though there is a potential link between fantasies and behavior. The aim of this study was to examine the frequency and contents of homicidal fantasies (targets, triggers, instruments, and emotional reactions) and their relation to substance abuse among 617 Finnish university students (mean age 24.2 years) contingent on gender. Sixty seven percent (n = 413) of respondents reported that they had experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Confirming (effective) sex invariance in the measure was an important step in its validation because sex differences in VIs represent a potentially important substantive issues: males vastly outnumber females as perpetrators of violence; however, our and previous studies would suggest that the homicidal/violent ideation differences are a long way from proportional to the perpetration differences (e.g. Auvinen-Lintunen et al, 2015;Kenrick & Sheets, 1993). For example, while males are responsible for approximately 80% of all homicides, they barely differed from females on VIS scores in the current study.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Confirming (effective) sex invariance in the measure was an important step in its validation because sex differences in VIs represent a potentially important substantive issues: males vastly outnumber females as perpetrators of violence; however, our and previous studies would suggest that the homicidal/violent ideation differences are a long way from proportional to the perpetration differences (e.g. Auvinen-Lintunen et al, 2015;Kenrick & Sheets, 1993). For example, while males are responsible for approximately 80% of all homicides, they barely differed from females on VIS scores in the current study.…”
Section: Discussionmentioning
confidence: 84%
“…For example, it likely that the predictive power of the VIS depends on a range of other situational and person factors. Given that VIs appear to be extremely common (Auvinen-Lintunen et al, 2015;Kenrick & Sheets, 1993;Bruns & Disorbio, 2000;Crabb, 2000;Grisso et al, 2000;Nagtegaal et al, 2006;Watt et al, 2013), identifying the factors that differentiate between PUBLISHED AS: Murray, A. L., Eisner, M., Ribeaud, D. Development and validation of a brief measure of violent thoughts: The Violent Ideations Scale. Assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the first studies to attempt to quantify this, the percentages of individuals in a student sample who experienced at least one homicidal ideation in their life so far were 79% for men and 53% of women (Kenrick and Sheets, 1993). Another, more recent study in a similarly ascertained sample reported analogous figures of 80.5% and 64.7% for men and women (Auvinen-Lintunen et al, 2015). Thus a key future direction will be to determine whether and at what points the frequency, severity or intensity of violent ideations becomes problematic.…”
Section: Discussionmentioning
confidence: 96%
“…Huesmann, 1988); can trigger negative emotional responses (e.g. Auvinen-Lintunen et al, 2015); and could undermine empathy (e.g. Anderson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%